Prognostic factors and survival in patients with hereditary hemochromatosis and cirrhosis - Beaton, Melanie D (Pulsus Group Inc, 2006)
OBJECTIVES: The survival of treated, noncirrhotic patients with hereditary hemochromatosis is similar to that of the general population. Less is known about the outcome of cirrhotic hereditary hemochromatosis patients. The present study evaluated the survival of patients with hereditary hemochromatosis and cirrhosis. METHODS: From an established hereditary hemochromatosis database, all cirrhotic patients diagnosed from January 1972 to August 2004 were identified. Factors associated with survival were determined using univariate and multivariate regression. Survival differences were assessed using the Kaplan-Meier life table method. RESULTS: Ninety-five patients were identified. Sixty patients had genetic testing, 52 patients (87%) were C282Y homozygotes. Median follow-up was 9.2 years (range 0 to 30 years). Nineteen patients (20%) developed hepatocellular carcinoma, one of whom was still living following transplantation. Cumulative survival for all patients was 88% at one year, 69% at five years and 56% at 20 years. Factors associated with death on multivariate analysis included advanced Child-Pugh score and hepatocellular carcinoma. Patients with hepatocellular carcinoma were older at the time of diagnosis of cirrhosis (mean age 61 and 54.6 years, respectively; P=0.03). The mean age at the time of diagnosis of hepatocellular carcinoma was 70 years (range 48 to 79 years). No other differences were found between the groups. CONCLUSIONS: Patients with hereditary hemochromatosis and cirrhosis are at significant risk of developing hepatocellular carcinoma. These patients are older when diagnosed with carcinoma and may have poorer survival following transplantation than patients with other causes of liver disease. Early diagnosis and treatment of hereditary hemochromatosis by preventing the development of cirrhosis may reduce the incidence of hepatocellular carcinoma in the future.